The Impact The Impact of E-Government Implementation and Leadership on Organizational Performance mediated by Employee Work Motivation at the Directorate General of Foreign Trade, Ministry of Trade - Redi Perdiansyah; Saluy, Ahmad Badawi; Novawiguna Kemalasari (Dinasti International Journal of Digital Business Management, 2022)
Abstract: This research finds out and analyzes the impact of E-Government Implementation and Leadership on Organizational Performance mediated by Employee Work Motivation at the Directorate General of Foreign Trade, Ministry of Trade. A quantitative method using primary data in the form of a survey. This research sample used was 162 employees. Data was collected using a questionnaire with a Likert scale of 1-5. The data analysis technique used is SEM with PLS software. The results of this study show; (1) Implementation of e-government has a significant effect on employee work motivation, (2) Leadership has no significant effect on employee work motivation, (3) E-government implementation has no significant effect on organizational performance, (4) Leadership has a significant effect on organizational performance, (5) Employee work motivation has a significant effect on organizational performance, (6) Employee work motivation significantly mediates e-government implementation on organizational performance, (7) Employee work motivation has no significant effect in mediating leadership on organizational performance.